Applying the Kirkpatrick-Model on evaluating an educational intervention about transfusion medicine among nurses. Preliminary results - Argyrou, Aspasia; Pouliakis, Abraham; Gafou, Anthippi; Tsoumakas, Konstantinos; Mariolis- Sapsakos, Theodoros; Fildisis, Georgios (Health & Research Journal, 2022)
Background: Implementation of systematic and sustainable training in theoretical and practical aspects of transfusion, maximizes transfusion-safety and improves quality of nursing services. Kirkpatrick-Model can be used effectively for evaluating such educational programs. Method and Materials: According to Kirkpatrick-Model, evaluation of educational programs is determined by four levels: 1st-Reaction, 2nd-Learning, 3rd-Behavior, 4th-Results. During years 2018-2019, an educational program about transfusion-medicine (presentations-lectures, brochures distribution, individual training) was implemented among nurses working mainly in an Oncology Hospital of the Hellenic National Health System. Demographics, educational/professional experience, knowledge-level on transfusion-medicine as well as suggestions for improving it, were checked with pre-and post-training questionnaires. Statistical analysis was made using SAS9.4-software for Windows/Excel 2007 (Kruskal-Wallis method for numeric parameters, x2-test for categorical). The significance level was set to P<0.05. Results: Regarding trainees’ reaction (level 1), 38.59% considered the educational program “satisfactory” (before training, 13.67% answered that they needed no training, after training 52.26%, P<0.05). Regarding learning (level 2), there was improvement in knowledge (14.2±3 correct answers/respondent before training, 21.1±1.8 correct answers/respondent post-training, 48.6% increase in correct answers/respondent, P<0.000001). The evaluation of the trainees' change of work-behavior due to training (level 3) will be performed through an extended observation-period by auditors using an extensive evidence-based observatory checklist. The overall outcome of training (level 4) will be assessed after completing the above-mentioned audits. Conclusions: According to Kirkpatrick-Model, the applied educational program is evaluated positively in terms of levels 1-2, as it was considered sufficient by trainees and improved their theoretical knowledge. Further evaluation in terms of levels 3-4 is an ongoing procedure.